An Analysis of Maxims in the Communication Between Teacher and Students During Online Learning by Zoom - Nomita Herlyna Manurung; Sondang Manik; Poster Sagala; Nurazizah (Jayapangus Press, 2020)
This study is purposed to describe maxims found in the communication between teacher and students during online learning by Zoom. In addition, this study is also aimed to describe the non-observance maxims made by the teacher and students. This study applied the descriptive qualitative approach of which the data were obtained from the recordings of learning process through Zoom meeting. The data were collected by using the video recordings and the transripts. The data then were analyzed to identify the types of the maxims and the non-observance maxims first, then classifying the maxims, and the last explaining the maxims and the non-observance maxims. The maxims that occurred in teacher and students’ conversation are maxims of quality, quantity, relevance, and manner. The result of the study shows that the there are 59 maxims. There are 43,75% utterances that obey the maxim of quality, 28,12% maxim of quantity, 18,75% maxim of relevance, and 9,37% maxim of manner. The non-observance maxim occurences are 40,74% on flouting maxim, 40,74% on opting out maxim, and 18,51% on violating maxim. This result indicates that teacher and students mostly obeyed maxim of quality in their conversation. In addition, flouting maxim and opting out maxim were frequently done by the teacher and students. Further research on maxims should be conducted in more kinds of data that involve a wider circle of participants